Food web structure of Nematode communities associated with rice in mwea,Kenya. - Mokuah, Dorcas Nyaboke (UoEm, 2023)
In Kenya, rice is an important staple crop after wheat and maize and the rate of consumption surpasses its production. Apart from consumption, rice is a cash crop for smallholder farmers including those in Kirinyaga County. Despite its usefulness in contributing to food security, rice production has remained low due to various constraints. Among these are plant-parasitic nematodes (PPN) that account for up to 20% of yield losses. Other than the deleterious effect of PPN, rice agroecosystems contain free living nematodes (FLN) that play important ecological roles such as decomposition of organic matter and suppression of destructive PPN. However, through various cropping practices, the diversity and structure of the nematode communities is altered which affects crop productivity. This study examined the abundance and additively partitioned diversity of nematode communitiesin rice in Mwea. Soil samples were collected from 30 rice fields in Nyangati (15) and Tebere (15) in Mwea, Kirinyaga county. Nematode extraction was done using the modified Baermann technique before enumeration and identification to the genus level. To determine the differences in the abundance of nematode genera, one-way analysis of variance (ANOVA) was used. Spatial distribution of nematode communities in Nyangati and Tebere wasexamined using Jaccard index-based non-metric multidimensional scaling.One-way ANOVA was used to evaluate the differences in the indices and metabolic footprints in Nyangati and Tebere. Gamma diversity was additively partitioned into α and β components in the R package vegan.Turnover and nestedness components of beta diversity were computed using the betapart package in R software. The relationship between soil properties and nematode genera was evaluated using canonical correspondence analysis. There were 17 nematode genera in both regions with Aphelenchoides and Longidorus occurring in greater proportions in Tebere.The population of Helicotylenchus was high in Nyangati and Prodorylaimus occurred in high numbers in both regions.Aphelenchoides was positively correlated to electrical conductivity while Helicotylenchus was negatively correlated.The two regions could not be unequivocally ordered due to crossing of the Renyi diversity profiles along the scale parameter.Genus richness partitioning, showed that α and β components contributed 33.7% and 66.3% of the γ diversity, respectively.Partitioning of beta diversity showed that nestedness contributed to the overall nematode diversity observed in Nyangati and Tebere rice fields.Results obtained from this study provide information that could aid in development and implementation of effective and environmentally sound nematode management practices in rice.
Keywords: Food web